English paragraph Writing at MTs Negeri 1 Morotai - Dwi Budidarma Sutrisno; Megawati Basri; Jasmal Martora (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service aims to educate the students at MTs Negeri 1 Morotai about English paragraph writing in four English class meetings conducted twice a week. 14 eighth grader junior high school students participated throughout the whole program. The activity applied lecture and game as the teaching method with one pre-test and one post-test. The topics during four meetings included vocabulary building, sentence writing, and paragraph writing. The game integrated cards with English words with five categories such as subject, predicate, object, complement, and connectors. The result shows (1) Overall, the students experienced increased scores from the Pre-Test to Post-Test (2) More specifically, half of the participants successfully answered half of the questions right during the Post-Test (3) Furthermore, the participants of the community service shows comprehension on vocabulary building, sentence writing, and paragraph writing. However, creating new sentences and a new paragraph are still considered challenging. For the word level questions, students showed maximum pre-test scores 10/10 and 5/10 increased into post-test scores 10/10 and 9/10. While for the sentence level questions revealed maximum pre-test scores 3/5 into 5/5. In contrast, paragraph level questions are mostly left unaswered for both pre-test and post-test. In other words, the English paragraph writing community service meets the expectation and is successful to some extent.